Educación ambiental para el manejo adecuado de envases de agroquímicos en la comunidad Estero Rosado - Álava Andrade, Johanna Estefanía (2021)
The present investigation was carried out in the “Estero Rosado” community, Flavio Alfaro canton, Manabí province; which aims to propose environmental education as a strategy for the proper handling of agrochemical containers. For its effect, it began with the diagnosis of the knowledge and environmental behavior of the residents of the community; conducting a situational analysis of the area using an observation sheet and applying an initial survey. Next, the environmental education strategy was established, which was developed in 3 days of training. Likewise, two surveys were carried out to determine the environmental knowledge and behavior of the residents, each one applied before and after the training. Finally, an Agrochemical Container Management Plan was prepared for the final disposal of pesticide containers that are generated in the community. As results, it was obtained that the initial environmental knowledge survey yielded the following: 38% BAD, 54% GOOD and 8% EXCELLENT; while, in the initial environmental behavior it was obtained: 51% REGULAR, 49% GOOD and 0% OPTIMAL. Once the environmental strategy was applied, these values had significant differences, in the final environmental knowledge with values of: 22% BAD, 67% GOOD and 11% EXCELLENT; in contrast to the final environmental performance that projected the following: 43% REGULAR, 54% GOOD and 3% OPTIMAL. Proving that positive changes were obtained both in knowledge and in the behavior of the inhabitants from the development of the training.